Funders and founders: partners in good times and in bad?. (2016) - Westerlund, Mika; Isabelle, Diane A.; Rajala, Risto; Leminen, Seppo
Based on a sample of 3097 small firms, we investigated how Finnish entrepreneurs perceive the relationship between corporate ownership structure and growth orientation. In particular, we investigated the type of ownership that entrepreneurs would provide to different types of funders in exchange for investment. Our empirical results suggest that the more growth-oriented the firm, the more accepting the entrepreneur of funders taking ownership that allows a strategic role in the company. Conversely, entrepreneurs in non-growth-oriented firms favour investors that will finance the operations without exerting power and influencing decision-making. Further, entrepreneurs in firms that are about to cease operations, generally due to weak economic conditions, are as likely to accept strategic ownership as high-growth-oriented firms. This study contributes to the literature by confirming the link between growth orientation and ownership structure in small firms, and by highlighting variations in entrepreneurial acceptance of different types of investor ownership.